Epidemiology of prostate cancer in South Korea - Hyun Ho Han (Prostate International, 2015)
Background: Prostate cancer (PCa) is the second most frequently diagnosed cancer in male. In South Korea, PCa incidence has increased significantly, while its mortality rate has decreased steadily. To optimize the distribution of public medical resources, it is essential to analyze the contemporary epidemiology of PCa. Methods: National population data from the National Health Insurance Statistical Yearbook and the annual report of national cancer registration and statistics in Korea were assessed. From the data, the incidence, prevalence, and mortality rates of PCa were calculated. The data were presented with reference to other types of cancers occurring in various countries from different continents. Results: From 2007 to 2013, PCa incidence doubled (from 5,516 per year to 10,855 per year), while its prevalence in Korean men tripled (from 18,830 to 51,411) during the same period. The mortality rate increased slightly, from 4.2 in 2000 to 5.9 in 2007 and 6.0 in 2013 (per 100,000, age adjusted). PCa incidence increased significantly faster in men aged < 70 years than in the older age group. Conclusion: PCa prevalence in South Korea has increased significantly, mainly due to the rise in its incidence. As the country is facing major changes, including westernization of dietary habits and rapid population aging, its prevalence would continue to increase in near future.